Evidence of sensorimotor deficits in functional ankle instability: A systematic review with meta-analysis - Munn, J.; Sullivan, S. J.; Schneiders, A. G. (Journal of Science and Medicine in Sport, 2010)
Functional ankle instability (FAI) has been associated with impaired sensorimotor function; however individual studies have produced conflicting results. In an attempt to reduce this ambiguity, a systematic review with meta-analysis was undertaken to determine which sensorimotor deficits exist with FAI. Fifty-three studies assessing sensorimotor factors in subjects with FAI were included from 465 identified articles. Studies were rated for methodological quality and data were pooled for peroneal reaction time, joint position sense, and postural sway during single-leg stance and time to stabilisation from a single-leg jump. Data on jointmovement sense were unable to be pooled. When subjects with unstable ankles were compared to healthy controls, sensorimotor impairments were demonstrated for passive joint position sense (mean difference (MD) = 0.7., 95% confidence interval (CI): 0.2.1.2., p = 0.004), active joint position sense (MD = 0.6., 95% CI: 0.2.1.0., p = 0.002), postural sway in single-leg stance (standardised MD (SMD) = 0.6, 95% CI: 0.2.1.0, p = 0.002), the star excursion balance test (SMD = 0.4, 95% CI: 0.1.0.7, p = 0.009), and time to stabilisation from a single-leg jump in a medio-lateral (MD = 0.6 ms, 95% CI: 0.4.0.8, p < 0.0001) and an antero-posterior direction (MD = 0.7 ms, 95% CI: 0.4.1.0, p < 0.0001). Peroneal reaction time was not affected. Sensorimotor deficits occur for joint position sense and postural control in subjects with FAI. Deficits in peroneal muscle reaction time following perturbation are not evident.